THE THEME OF WAR IN THE LITERARY AND JOURNALISTIC WORKS OF JAVIER CERCAS (Based on the Novels Soldiers of Salamis and The Speed of Light and Columns in El País Semanal) - Artemova, Lyudmila (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
This research presents the results of the analysis of the translations of different information materials (from Spanish into Ukrainian) carried out by the students of the Faculty of Translation and Interpreting of the University of Granada (Spain) under the teaching supervision for the II Conference on the Interpretation of the Language of Wine (24-25 April, 2023). In this article we would like to present the results of that enriching experience in many ways, since it offered us a perfect opportunity to approach the study of the peculiarities of the language of wine. It is a specialized language characterized by a series of unique and singular features that make its texts heterogeneous and hybrid. These texts fulfil multiple functions (informative, appellative, aesthetic, to name but a few) and, as a consequence, they bring together the peculiarities of different registers (legal and artistic, among others). Seen from a translatological perspective, the same relevant features make the translation of this typology of specialized texts a challenge, since their uniqueness is based on the fact that they combine a high percentage of terms specific to the field of wine with the complicated syntax and metaphorization of the text. _____________ References: • Cabré, T. La terminología: representación y comunicación. Elementos para una teoría de base comunicativa y otros artículos (Barcelona, Universitat Pompeu Fabra, 1999), 349 p. • Lehrer What’s new in wine language? En Proceedings of the first international workshop on linguistic aproaches to food and wine description (Actas del primer congreso internacional sobre aproximaciones lingüísticas a la descripcíon de la comida y del vino): (ed.), Goded Rambaud, M. (Madrid, 2013): 34-51. URL: https://elibro.net/es/ereader/ ugr/48686?page=40. • Montero Martínez S., Faber Benítez P., Buendía Castro M. Terminología para traductores e intérpretes? 2ª ed. (Granada: Ediciones Tragacanto 2011), 264 p. • Noya Gallardo La terminología vinícola jerezana en inglés (Cádiz, Servicio de Publicaciones Universidad de Cádiz, 1993), 384 p. • Ramírez Almansa El mundo del vino. Textos, terminología y traducción (Alemán-Español) (Granada: Editorial Comares, 2021), 147 p.